Airy's Functions in Non local Elasticity - (:unkn) unknown (AMER SCIENTIFIC PUBLISHERS, 2011)
Nanostructured devices and materials, such as carbon nanotubes, Atomic Force Microscope, MEMS, etc. attract increasing attention in the scientific world. It has been realized that the classical elasticity is not capable to capture the mechanical behavior of them precisely. There is a wide consensus among the scientists that nonlocal elasticity is more capable than the classical counterpart to model the mechanical behavior of nanostructured materials and devices. In this paper a method which is useful for solving problems in nonlocal is introduced. Airy's stress functions for plane stress problems in nonlocal elasticity are studied. The nonlocal constitutive equations in integral form are discussed and a method is suggested to invert the constitutive equation which allows expressing strains in terms of stresses. A qualitative discussion is given on this inversion process. For the nonlocality kernel of exponential form, the differential equation for Airy's functions in nonlocal elasticity is obtained by introducing the strains into the compatibility condition. Appropriate polynomial forms for the Airy's function are considered and are applied to solve beam bending problems. The solutions are compared with their classical counterparts. The results are given in a series of figures and tables and are discussed in detail. This paper is concluded by indicating the implications of the presented study in nanomechanics and nanotechnology.
Keywords: Nanomechanics; Nanotechnology; Non local Elasticity; Airy's Stress Functions; Bending of MEMS